2010
DOI: 10.1111/j.1365-2117.2009.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards ground truthing exploration in the central Arctic Ocean: a Cenozoic compaction history from the Lomonosov Ridge

Abstract: The Integrated Ocean Drilling Program's Expedition 302, the Arctic Coring Expedition (ACEX), recovered the first Cenozoic sedimentary sequence from the central Arctic Ocean. ACEX provided ground truth for basin scale geophysical interpretations and for guiding future exploration targets in this largely unexplored ocean basin. Here, we present results from a series of consolidation tests used to characterize sediment compressibility and permeability and integrate these with high‐resolution measurements of bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 74 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…O'Regan et al () suggested that the ridge remained at or near sea level during the duration of the time gap. Based on an analysis of the consolidation, strength, and permeability of the sediments recovered, O'Regan et al () suggest that the hiatus arose from a period of prolonged low to nondeposition. The cause of nondeposition and/or erosion has been attributed to tectonic uplift, either as a result of mantle phase changes (Minakov & Podladchikov, ) or as a result of the Eurekan orogeny, which reached its peak during the Eocene (Døssing et al, ).…”
Section: Geological and Oceanographic Settingmentioning
confidence: 99%
“…O'Regan et al () suggested that the ridge remained at or near sea level during the duration of the time gap. Based on an analysis of the consolidation, strength, and permeability of the sediments recovered, O'Regan et al () suggest that the hiatus arose from a period of prolonged low to nondeposition. The cause of nondeposition and/or erosion has been attributed to tectonic uplift, either as a result of mantle phase changes (Minakov & Podladchikov, ) or as a result of the Eurekan orogeny, which reached its peak during the Eocene (Døssing et al, ).…”
Section: Geological and Oceanographic Settingmentioning
confidence: 99%
“…There are three primary petrophysical properties that are required to calculate heat flow from a BSR; the compressional wave velocity, bulk density and thermal conductivity. In this model we use published compaction trends from sediments at ACEX [ O'Regan et al , 2010] to develop a porosity‐depth function, and use this to calculate the integrated density and thermal conductivity of the overlying sediment column. Each of the steps and assumptions in constructing the model are outlined below.…”
Section: Methodsmentioning
confidence: 99%
“…Concordant with this observation is a more gradual change in the modeled compressional wave velocities, which led to the suggestion that this segment of the Lomonosov Ridge was at initially deeper water depths during rifting from Barents‐Kara shelf [ Jokat , 2005]. Within seismic Unit I there is no indication of either an unconformity or a large‐scale shift from biosiliceous to glaciomarine sediments in the interpreted Cenozoic cover, and it remains possible that the current boundary between the two primary seismic units is younger, and is related to either the end of basin‐wide biosiliceous and organic rich sedimentation in the middle Miocene or alternatively represents the ongoing conversion of Opal A to C/T [ O'Regan et al , 2010]. However, irrespective of the age of this boundary, the BSR identified on these lines occurs at a relatively constant depth of ∼200 ms, and falls near the top of the Cenozoic sequence within Miocene or younger sediments (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…However, the latter correlation is of questionable value as the late Paleocene-early Eocene depositional environment on the shallow Lomonosov Ridge most likely differed from the older and deeper Mendeleev and Alpha Ridges. Also the thermal and subsidence history of Lomonosov Ridge are different from Mendeleev and Alpha Ridges and leave open any associations of the lower reflection bands on Mendeleev and Alpha Ridges with Opal A to Opal CT transition as suggested for Unit 2/3 transition in the ACEX core from Lomonosov Ridge (O'Reagan et al 2009). The age of the oldest sediments above acoustic basement on the Mendeleev and northwestern Alpha Ridges is estimated to be *70-75 Ma from the thickness (*0.20-0.25 s) below the top of MRB2 and ARB3 (Fig.…”
Section: Implications Of An Inter-ridge Stratigraphic Correlationmentioning
confidence: 97%
“…These upper layers isolate the warmer, more saline waters of Atlantic origin below and inhibit melting of the sea ice cover. The oceanic circulation in the present Arctic Ocean is characterized by low kinetic energy and weak cyclonic boundary currents (Rudels et al 1994;Jones 2001;Woodgate et al 2007). The boundary current flow (Fig.…”
Section: Ocean Circulationmentioning
confidence: 99%